Are exercises with or without occlusal splints more effective in the reduction of pain in patients with temporomandibular disorders of myogenic origin? A systematic review - Jessica Fernanda de Oliveira Lima BATISTA; Taciana Emília Leite VILA-NOVA; Sandra Lúcia Dantas MORAES; Eduardo Piza PELLIZZER; Belmiro Cavalcanti do Egito VASCONCELOS; Jéssica Marcela de Luna GOMES; Cleidiel Aparecido Araújo LEMOS; Mônica Vilela HEIMER (University of São Paulo, 2023)
Abstract Temporomandibular disorders (TMD) is a term used to describe a set of clinical conditions that may compromise the temporomandibular joint (TMJ) and masticatory muscles and/or associated structures, considered the most frequent cause of orofacial pain of non-dental origin. In recent years, many forms of physical therapy have been used in the treatment of TMD to reduce pain and improve the range of mandibular movement present in this impairment. Among these resources are kinesiotherapy (exercise), electrothermal and manual therapy, acupuncture, training posture, mobilizations, and biofeedback. Objectives To determine if exercises with or without occlusal splints are effective in reducing pain in patients with temporomandibular disorders (TMD) of myogenic origin. Methodology This systematic review was registered in the International Prospective Register of Systematic Reviews (CRD 42019134244). Controlled trials published in PubMed, Scopus, and Cochrane Library following PRISMA guidelines up to April 2022 were randomized and included. The population above 18 years, which evaluated the effectiveness of exercise with or without occlusal splints in reducing pain in patients with TMD of myogenic origin, diagnosed through the Research Diagnostic Criteria for Temporomandibular Disorders, was also included. There was no restriction on the period of publication. Cochrane risk of bias analysis was performed. Results Of the five included articles, all showed a reduction of pain, but without significant differences between the interventions performed. Additionally, studies that evaluated the quality of life and mandibular movements showed a reduction in pain, but no significant differences between therapies. Conclusion The analyzed studies showed no difference in the improvement of pain, quality of life, and mandibular movements between the groups that performed only exercises or the associated treatments.